Detectability of newborn chirp-evoked ABR in the frequency domain at different stimulus rates. (October 2013) - Cebulla, Mario; Stürzebecher, Ekkehard
Abstract: Objective: The present paper reports the results of a study on a group of newborns whose chirp-evoked auditory brainstem responses (ABR) were recorded at different repetition rates. The study was aimed at finding an optimum repetition rate for the chirp stimulus that facilitates a short response detection time in the frequency domain. Design: Chirp-evoked ABR were recorded at six different stimulation rates between 20/s and 100/s. The stimulation level was 35 dB nHL. The mean harmonic related SNR was calculated, and the response detection time and rate were assessed using a detection algorithm. Study sample: A group of 80 sleeping and 27 awake newborns with normal hearing were included. Results: The highest mean harmonic-related SNR in both groups was found at 60/s. The signal-to-noise ratio (SNR) was significantly smaller for the awake newborns. A significantly shorter detection time can be achieved for both newborn groups at 60/s compared to the other rates tested. Response detection in the group of awake newborns profited more from the change to 60/s compared to the sleeping newborns. Conclusions: It can be expected that with this optimized stimulus paradigm a shorter test time and a higher specificity of the hearing screening can be reached.